Management of the Kraków Functional Urban Area, in Poland, using a European Union Instrument: Integrated Territorial Investments - Noworól, Aleksander (Journal of Public Governance, 2019)
The objective of this paper is to analyse the ways in which one of the European Union’s Cohesion Policy instrument, i.e. the Integrated Territorial Investment (the ITI), can be used, with specific reference to the example of the Kraków Functional Urban Area (the KFUA). ITI is an instrument of EU policy and was introduced during the 2014–2020 program period. It was designed to promote the development of functional areas, especially on a metropolitan scale, and to strengthen the co-operation ability of local entities. Research design: The reasoning utilised in this article uses participant observation as the primary research method. The complimentary analytical methods are desk research of documents, written questionnaires and individual direct interviews. It is important to underline the direct involvement of the author in the preparation of the ITI Strategy for the KFUA, participative workshops concerning the introduction of ITIs, and expert reports commissioned by the Kraków Metropolis Association (the KMA). The findings enable one to clarify mechanisms disclosed in the national scale with specific features also present in the KFUA. The first part of this paper includes a brief review of the literature concerning the nature of the metropolitan scale, management of the development of functional urban areas, and deliberation procedures. In the second part, the author presents the results of his qualitative research revealing the way an instrument of ITI is implemented by the KMA. Tools used by the KMA, taking into consideration juridical and cultural conditioning, demonstrate how the ITI instrument can become, beyond financial support for communities, a real creator of a co-operative ecosystem of entities. The added value is to show that the ITI instrument, despite some bureaucratic sluggishness, can be, thanks to understanding the essence of “metropolitan governance”, an approach which builds real territorial co-operation.